Hubungan Dukungan Suami Dengan Persiapan Menghadapi Persalinan Pada Ibu Usia Remaja - Aryawati, Luh Putu; Senjaya, Asep Arifin; Mahayati, Ni Made Dwi (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
The increasing incidence of teenage marriage each year will pose psychological risks regarding readiness and adjustment to the new role of motherhood. The impact that can occur due to immature physical and reproductive organs causes risky pregnancy and childbirth. This study aims to determine the relationship between husband's support and childbirth preparation in teenage mothers in Negara District. The researcher used a quantitative analytical correlational cross-sectional approach. Sampling involved 46 teenage pregnant mothers using the total sampling method. Data analysis was conducted using univariate and bivariate methods, with the chi-square test. The results showed a p-value = 0.01, meaning there is a relationship between husband's support and physical readiness for childbirth in teenage mothers in Negara District. The OR value = 4.88 means that teenage pregnant women who do not receive support from their husbands are 4.9 times more at risk of being unprepared for childbirth. It is important for the community to raise awareness about the role of husbands in supporting their wives during pregnancy. Health education programs involving husbands and partners can help increase the support provided.